What every Christian needs to know about the Jewishness of Jesus : a new way of seeing the most influential rabbi in history - Moffic, Evan, 1978- (Nashville, TN : Abingdon Press, 2015)
If you were to ask ten people, Who started Christianity? you might hear ten voices giving the same quick response: Jesus. But those ten people would be wrong. Jesus wasn't a Christian. Jesus lived and died as a Jew. Understanding the Jewishness of Jesus is the secret to knowing him better and understanding his message in the twenty-first century. Walking through Jesus' life from birth to death, Rabbi Evan Moffic serves as a tour guide to give Christians a new way to look at familiar teachings and practices that are rooted in the Jewish faith and can illuminate our lives today. Moffic gives fresh insight on how Jesus' contemporaries understood him, explores how Jesus' Jewishness shaped him, offers a new perspective on the Lord's Prayer, and provides renewed appreciation for Jesus' miracles. In encountering his Jewish heritage, you will see Jesus differently, gain a better understanding of his message, and enrich your own faith.
A humble birth -- An unexpected turn -- Entering the waters -- Surviving a wilderness of temptations -- Calling the disciples -- Do you believe in miracles? -- Finding honey on the page -- The Shema -- The Lord's Prayer -- The last days -- Five rabbis explain Jesus.
Includes bibliographical refereneces (pages 185-188).
Includes chapter 1 of the author's "What every Christian needs to know about Passover" (pages 189-203)
Keywords: Jesus Christ -- Biography; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Jesus Christ -- Jewishness; Jesus Christ -- Jewish interpretations